The Word Angel in Old and Contemporary Biblical and Koranic Translations - Kulwicka-Kamińska, Joanna (Slavistica Vilnensis, 2009)
The purpose of this article is to investigate the etymology of the word angel in Polish biblical and Koranic translations as well as the ways of its translation from Hebrew, Greek and Arabic into religious texts. The author examines whether the phraseological connections of the word angel (which is used by Lithuanian and Polish Tartars and in the Polish translations of the Koran) are specific for this genre of literature in the production of the Koranic phraseology. To establish the range and nature of the connections between the biblical and Koranic translations, the author considers whether and to what extent they reflect biblical or Polish phraseology.